Combining ability analysis for yield and contributing traits in short duration rice (Oryza sativa L.) - Singh, Vineeta; Dwivedi, DK; Khan, NA; Verma, RL; Kumar, Manish; Jena, Debarchana; Rout, Diptibala; Arsode, Pandurang; Samantaray, Sanghamitra (ORYZA-An International Journal of Rice, 2021)
The breeding value is an important genetic parameter determines utility of lines/genotypes to be used as parent in breeding program. This study was aimed at dissecting the breeding values (combining abilities) in 8 short duration rice lines for yield and 15 attributing traits. Altogether, 28 F1s developed under half-diallel fashion along with eight parents were evaluated. The study revealed importance of both additive and non-additive gene effects in governing yield and yield components with preponderance of non-additive gene action for most of the yield components. Additive gene action was found important for 1000-grain weight. The parental genotype (NUD3) and (NDR 359) were found to be good general combiners. The hybrids namely NDR359/Sarjoo-52, NDR359/NUD2, NDR359/NDRK5088, NDR359/NDR1, NDR359/Nagina22, NDR359/NUD3, NDR359/CSR10, Sarjoo52/NDRK5088, Sarjoo52 X NDR 1, NUD 2/NDR1, NUD 2/NUD3, NDRK5088/Nagina22, NDRK5088/ NUD3, NDRK5088/CSR10, NUD 3/Nagina 22, Nagina 22/NUD3, NUD3/CSR 10 have shown significant favourable sca effect for yield and different yield components.